Ландшафт і його теоретичні інтерпретації - Мартіненайте, Л. (Народна творчість та етнологія, 2011)
The article aims to reveal the concept of landscape and its interpretations by the Lithuanian and foreign researchers. Using analytical comparative method, examined are the aspects of landscape studies’ development in the foreign and Lithuanian research works. The author presents theoretical approach to the characteristics of Lithuanian rural landscape and reveals the new research aspects.